2023
DOI: 10.3390/ijms24032421
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Senescent Markers in Small Extracellular Vesicles

Abstract: Senescent cells exhibit several typical features, including the senescence-associated secretory phenotype (SASP), promoting the secretion of various inflammatory proteins and small extracellular vesicles (EVs). SASP factors cause chronic inflammation, leading to age-related diseases. Recently, therapeutic strategies targeting senescent cells, known as senolytics, have gained attention; however, noninvasive methods to detect senescent cells in living organisms have not been established. Therefore, the goal of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In addition to other SASP factors, senescent cells can release small extracellular vesicles (EVs), including exosomes. Molecules in EVs obtained from the blood could be novel gerodiagnostic markers [76,77]. The microRNA (miRNA) expression and secretion profile of senescent cells has recently come into the spotlight [78,79].…”
Section: Markers Of Cellular Senescencementioning
confidence: 99%
“…In addition to other SASP factors, senescent cells can release small extracellular vesicles (EVs), including exosomes. Molecules in EVs obtained from the blood could be novel gerodiagnostic markers [76,77]. The microRNA (miRNA) expression and secretion profile of senescent cells has recently come into the spotlight [78,79].…”
Section: Markers Of Cellular Senescencementioning
confidence: 99%
“…It has been suggested that the inclusion of the WRN gene in genetic analyses for early-onset diabetes, lipodystrophy, or dyslipidemia may offer an opportunity to diagnose patients with Werner syndrome long before the presentation of the full spectrum of symptoms and complications, enabling earlier interventions, including malignant neoplasm screenings and prevention of diseases listed in the clinical criteria [ 58 ]. Recently, novel senescent markers, ATP6V0D1 and RTN4, were shown to be increased in cells derived from patients with Werner syndrome, raising a possibility that they may serve as markers of disease progression [ 59 ]. Similarly, ribonuclease H2 subunit A (RNaseH2A) was shown to be downregulated in Werner syndrome cells as well as selected cancer cells [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…EVs are involved in diverse biological processes, such as cell motility [ 254 , 255 , 256 ], differentiation [ 257 , 258 , 259 ], proliferation [ 260 , 261 ], apoptosis [ 262 , 263 ], reprogramming [ 264 , 265 , 266 ], and immunity [ 267 , 268 ], through regulation of intercellular communication. Understanding the regulatory mechanisms of EVs in these biological processes and in intercellular communication is crucial for their clinical potential [ 269 , 270 ] and applications [ 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 ].…”
Section: Pharmacology Of Extracellular Vesiclesmentioning
confidence: 99%